Kebijakan Kepala Madrasah dalam Meningkatkan Karakter Kedisiplinan Belajar Siswa di MTsN 4 Padang Lawas - Mesiono Mesiono; Inom Nasution; Tria Indah Ristika (Jurnal Budi Pekerti Agama Islam, 2024)
The research carried out was entitled "Policy of the Madrasah Principal in Improving the Disciplinary Character of Student Learning at MTsN 4 Padang Lawas", which was motivated by the lack of implementation of the disciplinary character of students in this madrasah. This proves that the Madrasah Principal's policy is needed as a leader in this madrasah to manage and implement the rules that have been implemented in the madrasah so that the disciplined character of student learning can run well. The research method uses qualitative research with a phenomenological approach. As a data source for this research, the researcher took several sources of information from the head of the madrasa, the deputy head of the madrasa for student affairs, one of the homeroom teachers, and one of the students at MTsN 4 Padang Lawas. The results of the research reveal that, 1) The Madrasah Head's policy in improving the disciplinary character of student learning at MTsN 4 Padang Lawas is implemented through four things, namely, a) Enforcement of rules and discipline, b) Creating a reward and punishment system, c) Supervision and monitoring, d) collaboration to create student interest in learning; 2) The level of student learning discipline in complying with the policy of the head of the medrasa at MTsN 4 Padang Lawas is implemented through two things, namely, a) student attendance in class, b) student compliance with madrasa rules; 3) Student learning motivation in learning discipline at MTs N 4 Padang Lawas covers two things, a) the level of student interest, b) the appreciation felt by students for the learning process; 4) Factors that influence improving the character of student learning discipline at MTsN 4 Padang Lawas include two things, namely, a) internal factors and b) external factors. Based on the results of the research above, the Policy of the Head of MTsN 4 Padang Lawas is very important in improving the disciplinary character of student learning at this madrasah. This is because the policy of the head of MTsN 4 Padang Lawas is something that can improve the quality of the madrasah.